Good news from newts: distribution, population size, and dynamics of two protected newt species in the Jiu Gorge National Park, Romania - Severus-Daniel COVACIU-MARCOV; Denisa-Marina POP; Felicia-Nicoleta SUCEA; George-Adelin ILE; Alfred-Ștefan CICORT-LUCACIU; Sára FERENȚI (Studia Universitatis Babeș-Bolyai. Biologia)
Long-time monitoring studies recently indicated that newts are in decline in many regions. Motivated by the above-mentioned, in the year 2019, we started monitoring the newt populations from the Jiu Gorge National Park (JGNP) in the Romanian Carpathians, 10 years after the previous study on the same topic. Compared with other areas where newts are in decline, we identified new distribution locations of the two newt species which are present in the park. Also, the previously known populations have greatly increased. Thus, the Lissotriton vulgaris population increased 2.58 times in 10 years, and the Triturus cristatus increased 1.80 times in 10 years. At the same time, in areas from JGNP affected by human activities in the past (abandoned quarry and areas adjacent to the railway), the newts extended their range in the last years and occupied artificial aquatic habitats. In the case of the populations from the natural habitat, the temporal dynamics and the ratio between sexes and species followed the same evolution as in the case of other populations from Romania. The increase of newt populations from JGNP in the last 10 years was most probably a consequence of the reduced human pressure, corroborated with the large surface occupied by native forests in the park. Thus, in natural areas, probably the best management measures for both newt species are not represented by direct (invasive) human interventions but by the conservation of the natural habitats used by the newts. A protected area should maintain the conservation status at least at the present level, and if the region is natural, this fact will maintain and also increase the newt and probably other amphibian populations.